Cardiology essentials in clinical practice - Adelmann, Gabriel A. (Springer-Verlag, 2011)
Being a cardiology fellow is one of the most daunting commitments one can make as a physician. The stressful and intensive work schedule is followed by long hours of study in an ever-expanding field, making it occasionally challenging to master both classical teachings and cutting-edge developments. Graphically memorable tables and schematics are one of the most useful tools for making sense of the profusion of guidelines, textbooks, and medical papers. The Cardiology Essentials in Clinical Practice provides these tools to those learning the practicalities of cardiology, whether as residents, fellows, or internists. In conjunction with the concisely conceived text, the tables and figures provide a comprehensive clinical picture of each condition, while reviewing key specific details. The text and tables have been grounded in the existing practice guidelines, while incorporating the results of the latest clinical trials. Key trials and resources have been outlined in the text and bibliography to facilitate follow-up on the issues of interest, making this manual an invaluable tool in the quest for a wide-ranging, yet precise knowledge of cardiology.